Fancy Nancy : Saturday night sleepover - O'Connor, Jane (Harper, an imprint of HarperCollinsPublishers, 2016)
Nancy and Jojo go on a sleepover, but since it's Jojo's first one, Nancy is determined to make it fun and put her at ease, but when it's time for bed, it's Nancy who grows nervous and needs the help of her sister.